O Professor Universitário Manuel de Melo Adrião. O Exemplo do Humanismo na Medicina. - Ana Raquel Lemos Lopes Teixeira (2021)
Introduction: Manuel de Melo Adrião, university teacher, medical doctor, father, and friend to the poor, dedicated himself irreproachably to clinical practice and university education. This dissertation aims to praise a doctor and university professor of enormous importance in Portuguese Medicine's History and the Faculty of Medicine of the University of Porto (FMUP). Methods: The bibliographical research was based on the documental collection of the Anatomy Museum, the Anatomy Archives, the General Library, the Maximiano Lemos Medicine History's Museum, organic units of the Faculty of Medicine of the University of Porto, on online contents and on several interviews with his daughter, Maria Fernanda de Melo Adrião, his grandson, Gustavo Mergulhão and Professor Levi Guerra. Results: Brilliant student, clinician of unusual merits, remembered by many for his intelligence, humor, and humility. Detached from materials and titles, he brilliantly conciliated the academic and clinical aspects, never forgetting those in need. Discussion: He promoted the training of several doctors, particularly Professor Abel Sampaio Tavares, his successor in the anatomy's professorship, and Professor Levi Guerra. He organized and belonged to the management bodies of numerous congresses and was a member of the Portuguese Anatomical Society, the Society of Anthropology and Ethnology, and the Paris' Société Anatomique. Conclusion: Distinguished university professor, respected doctor, exemplary citizen, Professor Melo Adrião is deeply remembered by his colleagues, disciples, and friends for his generosity to patients, his material unattachment, but mainly for his medical personality gifted with extraordinary teaching and innovation capabilities allied to a total dedication, attributes that fully personify the persons dedicated to science and Medical School where he professed.